Formulation development and evaluation of medicated chewing gum of anti-emetic drug - Mansi Paradkar; Balaram Gajra; Bhautik Patel (Elsevier, 2016)
Context: Medicated chewing gum (MCG) of Domperidone Maleate (DM) was developed by direct compression method with the goal to achieve quick onset of action and to improve patient compliance. Objective: Formulation development of MCG of DM and optimization of the formulation by screening of different excipients. Material and methods: MCG containing DM was prepared by screening different concentrations of sweeteners, flavouring agents, softening agents, lubricants and anti-adherents by changing one variable at a time. Performance evaluation was carried out by evaluating size, shape, thickness, taste, scanning electron microscopy, texture analysis, in vivo drug release study, ex vivo buccal permeation study and by studying statistical analysis for quality. Results and discussion: The statistical analysis showed significant improvement in organoleptic properties such as chewable mass, product taste, product consistency, product softness, total flavour lasting time and pharmaceutical properties like micromeritic properties after incorporation of appropriate excipients in an optimum amount in final optimized MCG formulation. In vivo drug release study showed 97% DM release whereas ex vivo buccal permeation study through goat buccal mucosa exhibited 11.27% DM permeation within 15 min indicating its potential for increasing bioavailability by decreasing time of onset. The optimized formulation showed good surface properties and the peak load required for drug release was found to be acceptable for crumbling action. Conclusion: The developed formulation of medicated chewing gum can be a better alternative to mouth dissolving and conventional tablet formulation. It may be proved as a promising approach to improve the bioavailability as well as to improve patient compliance.